Implementation of sparkol videoscribe physics-based learning media pace to improve students' analytical skills - Umi Pratiwi; Resti Asih Setyaningrum; Eko Setyadi Kurniawan (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
Learning media can determine the quality of education, one of the digital media revolution with the development era 4.0. So that the required media interesting and appropriate media learning needs. One of the instructional media used is a dynamic learning media and digital nature, i.e., sparkol videoscribe instructional media as media that is flexible. This study aims to determine the ability to analyze the learners after the learning intervention with learning models Project, Activity, Cooperative Learning, Exercise (PACE) class X Mathematics learners SMAN 6 Purworejo. This study used a quasi-experimental design with pre-test and post-test. The results showed that the average value of the pre-test students on the material Enterprises and Energy before the implementation of PACE is learning to use the model of implementation is 46.28 and after 80.75. The highest post-test value of 95 indicated by the attribute aspect. The amount of the lowest post-test that is 72 represented by aspects of organizing the linking indicator of a problem.